New modalities for non-invasive positive pressure ventilation: A review article - shahram seyfi; parviz amrimaleh; simin mouodi (Babol University of Medical Sciences, 2019)
Efficiency of non-invasive positive pressure ventilation in the treatment of respiratory failure has been shown in many published studies. In this review article, we introduced new modalities of non-invasive ventilation (NIV), clinical settings in which NIV can be used and a practical summary of the latest official guidelines published by the European Respiratory Clinical Practice. Clinical trials and review articles in four databases up to 25 February 2018 about new modalities of non-invasive positive pressure ventilation were reviewed. Commonly used modalities for treatment of respiratory failure include: CPAP (continuous positive airway pressure) and BiPAP (bilevel positive airway pressure) or NIPSV (noninvasive pressure support ventilation). The limitations of the BiPAP method are the trigger and cycle asynchrony, inadequate volume delivery and increased respiratory rate. Newer methods, such as adaptive servo-ventilation, have been developed to treat central and complex sleep apnea and the NAVA (neutrally adjusted ventilatory assist) to improve the trigger and cycle asynchrony. In the proportional assist ventilation, unlike the pressure support ventilation, with increased patient effort (flow) the tidal volume increases and it prevents the increase in the respiratory rate and respiratory distress. High-flow nasal cannula is a non-invasive technique that does not provide respiratory support, but provides a mixture of oxygen to the patient. The use of non-invasive pursed-lip breathing ventilation in chronic obstructive pulmonary disease (COPD) patients reduces dyspnea (decreases respiratory rate) and increases blood oxygen saturation. New modalities of NIV improve patient comfort and patient-ventilator interactions, and are recommended in patients with respiratory failure.